Distributed Authentication in a Multi-Zone Direct Acyclic Graph Blockchain for IoT Environment - Kably Salaheddine; Benbarrad Tajeddine; Alaoui Nabih; GuerreroGonzálezoz Antonio; Arioua Mounir (ITM Web of Conferences, 2023)
This research paper presents an indepth examination of the security aspects of the Multiple Zone Direct Acyclic Graph Blockchain (MZ-DAG Blockchain) framework. The MZ-DAG Blockchain features a security layer that implements a non-clonable physical function-based validation mechanism for the authentication of multiple certificates within the blockchain. To enhance the security of this layer, this study proposes the integration of a lightweight intrusion detection system specifically designed for the MZ-DAG Blockchain. This work is a contribution to the ongoing efforts to secure and streamline the implementation of blockchain networks in resourceconstrained environments.